O estado da arte do direito ao esquecimento na sociedade da informação : a colisão com as liberdades comunicativas e a busca por soluções jurídicas - Silva, Ana Carolina Leite da (2021)
This research arises from the need to understand how the existing conflict occurs, and even more evident in the Information Society, between the right to communicative freedoms and the right to be forgotten. In the Information Society, the only certainty is the constant change: in social, political, economic and technological transformation. Amidst this whirlwind of changes, human relations also find new perspectives and, driven by virtuality, they start to happen more and more quickly. It is in this scenario that the need for new protection mechanisms arises, resulting in previously unheard means of providing legal assets such as life, image and individuality. The right to be forgotten appears as a possible protective mechanism, in order to safeguard the individual in the current conjuncture of media exaggerations and the world wide web. The main objective of this research is to study and understand the way in which this apparent conflict between fundamental rights takes place, what are its contours, how law operators have been working to resolve this conflict and whether there is a need to establish new parameters so that it is possible to reach a solution to the problem; all of this having the Information Society as background. For that, the method adopted will be the hypothetical-deductive, considering as main hypothesis the existence of a conflict between the right to forget and the communicative freedoms in the era of superinformationism, which would generate the need to establish a coherent and comprehensive legal parameter in instance to achieve harmonious coexistence among those. It is intended to divide the research into three parts, the first being dedicated to the setting of the aforementioned rights in the Information Age, the second to an indepth study of the legal conflict addressed and, finally, the analysis of how the subject has been treated by legislation national and national courts. Bibliographic research is used, based on the study of civil and constitutional law, as well as documentary analysis for the investigation of legislation and jurisprudential production that has been carried out. The research identified that the right to be forgotten has been used more and more in the courts of justice as a mean to obtain protection for the individual's privacy and past, in order to protect him from the abuses that can be committed in the exercise of freedoms such as expression and information. Furthermore, there was also verified a latent divergence between the judicial decisions that deal with the conflict between personality rights and communicative freedoms, which culminated in the analyse of the Supreme Court judgment on the subject. Finally, it is noteworthy that the present study sought to enrich the debate in a field that is still fertile and little explored in Brazilian law.